Effect of sorghum flour composition and particle size on quality of gluten-free bread - Frederick, Emily J. (Kansas State University, 2009)
In order to improve the quality of products available for consumers who require a gluten-free diet, this study examined the effects of sorghum flour composition and particle size on functionality in gluten-free batter bread. White, food-grade sorghum was milled to flour of varying extraction rates (60%, 80%, 100%), and was subsequently pin-milled at different speeds (no pin-milling, low- speed, and high-speed) to create flours of both variable composition and particle size. Two commercially-milled sorghum flour samples (AF and TV) were included in the study and subjected to the same pin-milling treatments. Characterization of each flour included measurements of flour composition, total starch content, particle size distribution, damaged starch, and water absorption. Bread characterization included measurement of specific volume, crumb properties, and crumb firmness through the use of digital imaging and texture profile analysis. Significant differences were found (p<0.05) in the composition of sorghum flours of varying extraction rate, most notably for fiber and total starch contents. Flour particle size and starch damage were significantly impacted by extraction rate and speed of pin milling (p<0.05). With the exception of the commercial flour samples, water absorption increased significantly with increasing extraction rate and speed of pin-milling speed (p<0.05). Within all treatments, breads produced from 60% extraction flour had significantly higher specific volumes, better crumb properties, and lower crumb firmness when compared to all other extractions and flour types. These measured bread characteristics were significantly impacted by flour properties, specifically particle size, starch damage, and fiber content (p<0.0001). The commercial flours studied produced breads of low specific volume, poor crumb properties, and dense textures. These results can assist millers and product developers in advancing the quality of sorghum-based gluten-free foods for the consumers that require them. Further research is necessary to better understand the extent to which particle size, and therefore starch damage, can improve sorghum-based gluten-free breads.
Keywords: sorghum; gluten-free; particle size; Agriculture, Food Science and Technology (0359)